Electron backscatter diffraction (EBSD) study of seven heavily metamorphosed chondrites: Deformation systematics and variations in pre-shock temperature and post-shock annealing. (1st August 2018) - Ruzicka, Alex M.; Hugo, Richard C.
Abstract: We used electron backscatter diffraction (EBSD) methods to study the crystallography of olivine and other minerals in seven heavily metamorphosed (petrographic type 6 or 6/7) but variably shocked ordinary chondrites from the H (Kernouvé, Portales Valley), L (Leedey, Bruderheim, Morrow County, Park) and LL (Miller Range (MIL) 99301) groups. MIL 99301 contains a large clast that was analyzed separately. Mesoscale (EBSD) data support and extend inferences based on microscale (TEM) observations and provide good evidence that chondrites were shock-deformed at different temperatures and were variably annealed (sintered) after deformation. Various EBSD deformation intensity metrics adequately and quantitatively represent olivine deformation in meteorites on different scales and in different ways. Mean Grain Orientation Spread ( GOS, the average misorientation in a grain) is a robust statistic for overall deformation. We developed an EBSD deformation temperature metric based on olivine misorientation rotation axis data, and an EBSD post-shock annealing metric based on the skewness of olivine GOS distributions. The two parameters together define three groups among the meteorites studied, and these are related to shock stages and 40 Ar/ 39 Ar ages that record impact times. Group 1 includes cold-deformed and little-annealed but high-shock-stage (S4 and S5) chondrites (Leedey, Bruderheim, Morrow County) that were affected by impacts at a time (<4 Ga ago) when parent bodies were cold. Troilite was deformed and partly recrystallized, developing a lattice preferred orientation (LPO) in Bruderheim and Morrow County that corresponds to a principal compression direction. Olivine 〈0 0 1〉 axes in Morrow County were partially re-oriented perpendicular to this compression direction. Group 2 includes the hot-deformed but little-annealed MIL 99301 clast that shows good evidence of having formed as a shock melt, and which represents localized shock heating of material that cooled rapidly at a time when parent bodies may have been cold (∼4230 Ma ago, assuming the younger of two published ages for MIL 99301, 4230 ± 30 and 4520 ± 80 Ma, corresponds to the clast). Group 3 includes hot-deformed and more-annealed low-shock-stage (S1) chondrites (Kernouvé, Portales Valley, MIL 99301 host, Park) that experienced impacts on warm bodies in the oldest epoch (>4425 Ma, assuming the older of two published ages for MIL 99301 corresponds to host). Group 3 chondrites must have been shocked while warm at the time of impact, at temperatures estimated as >700–800 °C and up to ∼1000 °C, i.e., at conditions generally corresponding to thermal metamorphism associated with petrographic type 6 grade, and were subsequently buried and annealed in warm parent bodies. Impact at elevated pre-shock temperature resulted in partly recrystallized troilite in Park and metallic liquids that crystallized as coarse troilite interstitial to silicates in Portales Valley. For Group 3, data are consistent with impact-redistribution on warm parent bodies that were hot at depth, and support a model of early collisional processing of endogenically-heated chondritic planetesimals. In general, EBSD deformation signatures in each of the meteorites studied are dominated by the effects of the prevailing impact, although there is some evidence for multiple impact effects.